Returns to University Quality in Australia: A Two-Stage Analysis - David Carroll; Christopher Heaton; Massimiliano Tani (Institute for the Study of Labor (IZA), 2014)
This study investigates the relationship between university quality and graduate starting salaries using pooled Australian data from the Graduate Destination survey and a two-stage estimation methodology. The results suggest that average starting salaries for young undergraduates differ significantly across universities after controlling for relevant confounding factors, though the range of university effects is fairly small in relation to other salary determinants, particularly course area. The results are robust to alternative specifications and suggest that employers generally do not place salary premia on attending a high-quality or prestigious university, at least upon workforce entry.
Keywords: A22; I23; J24; 330; human capital; returns to education; university choice